The winner takes it all: The mediating role of competitive orientations in the Dark Triad and sport task performance relationship - Vaughan, R. S.; Madigan, D. J. (European Journal of Sport Science, 2021)
The Dark Triad traits (Machiavellianism, narcissism, and psychopathy) are prevalent in athletes. However, currently, we do not know whether the Dark Triad confers any competitive advantages in sport. To address this issue, the present study had two aims. First, to examine whether the Dark Triad predicted task performance in a basketball free throw task. Second, to examine whether competitive orientations explained (i.e. mediated) this relationship. A sample of 189 athletes (mean age = 19.11 years) completed measures of the Dark Triad, competitive orientations, and task performance (basketball free throw task). Regression analyses indicated that the Dark Triad predicted better task performance. In addition, mediation analyses indicated that the Dark Triad-performance relationship was explained by both hypercompetitive and self-developmental competitive orientations. The present study provides the first evidence that the Dark Triad may lead to better task performance in sport, and that this effect may be driven by athletes` competitive orientations.